Comparative Analysis of Quality and Environmental Management Strategic Implementation in Cement Industry - Filson Maratur Sidjabat; Risalatul Habibah; Martogi Pasaribu (Media Ilmiah Teknik Lingkungan (MITL), 2019)
The cement industry's activities have an impact on health and the environment, therefore a solution is needed to deal with the negative impacts of the cement industry operations. The cement industry undertaken various strategies in dealing with the negative impacts that occur to remain trusted by buyers. The strategy carried out by the cement industry is not only according to national standards but also international standards. ISO is one of the international standards in operational activities. The cement industry strives to obtain ISO 9001: 2015 certification regarding quality management which ensures the quality of cement products is in accordance with international standards and ISO 14001:2015 certification regarding environmental management which ensures that the industrial strategy implemented by the industry is in accordance with international standards. Three cement industries in Indonesia that have been certified ISO 9001: 2015 and ISO 14001: 2015 are PT Indocement Tunggal Prakarsa Tbk., PT Holcim Indonesia Tbk., And PT Semen Baturaja Tbk. The author will analyze the comparison of strategies implemented by the three cement industries in implementing ISO 9001: 2015 and ISO 14001: 2015. The method used in this research is descriptive exploratory. The collection of data and information is carried out through several references from related companies.